Quantitative Analysis of Dynamic Body Patterning Reveals the Grammar of Visual Signals during the Reproductive Behavior of the Oval Squid Sepioteuthis lessoniana - Lin, Chun-Yen; Tsai, Yueh-Chun; Chiao, Chuan-Chin (Frontiers in Ecology and Evolution, 2017)
Cephalopods use a diverse range of body patterns for visual communication. Each pattern is composed of several distinct chromatic components that are under neural control and are expressed dynamically. In the oval squid Sepioteuthis lessoniana, males use distinct body patterns to interact with females and other males at the spawning site. To systematically examine their visual signals during reproductive behavior, an ethogram of 27 body pattern components produced by S. lessoniana was observed in both the wild and captivity; these were then characterized. Five behaviors were commonly seen among these reproductively active squids, namely parallel swimming, male guarding, male-male fighting, male-parallel mating, and male-upturn mating. Each behavior was found to be composed of the expression in a temporal sequence of different chromatic components. By analyzing the dynamic body patterning time series associated with each behavior, it was found that a certain subset of components was expressed simultaneously or sequentially in response to conspecifics. Importantly, the results not only revealed that each behavior is composed of multiple chromatic components, but the findings also showed that each component is often associated with multiple behaviors. To gain insight into the visual communication associated with each behavior in terms of the body patterning's key components, the co-expression frequencies of two or more components at any moment in time were calculated in order to assess uniqueness when distinguishing one behavior from another. This approach identified the minimum set of key components that, when expressed together, represents an unequivocal visual communication signal. While the interpretation of the signal and the associated response of the receiver during visual communication are difficult to determine, the concept of the component assembly is similar to a typical language within which individual words often have multiple meanings, but when they appeared together with other words, the message becomes unequivocal. The present study thus demonstrates that dynamic body pattering, by expressing unique sets of key components acutely, is an efficient way of communicating behavioral information between oval squids.